Delayed presentation of a sigmoid colon injury following blunt abdominal trauma: a case report - Ertugrul Gokhan; Coskun Murat; Sevinc Mahsuni; Ertugrul Fisun; Toydemir Toygar (Journal of Medical Case Reports, 2012)
Abstract Introduction The low incidence of colon injury due to blunt abdominal trauma and the lack of a definitive diagnostic method for the same can lead to delays in diagnosis and treatment, subsequently resulting in high morbidity and mortality. Case presentation A 66-year-old woman with sigmoid colon injury was admitted to our emergency department after sustaining blunt abdominal trauma. Her physical examination findings and laboratory results led to a decision to perform a laparotomy; exploration revealed a sigmoid colon injury that was treated by sigmoid loop colostomy. Conclusions Surgical abdominal exploration revealed gross fecal contamination and a perforation site. Intra-abdominal irrigation and a sigmoid loop colostomy were performed. Our patient was discharged on post-operative day six without any problems. Closure of the sigmoid loop colostomy was performed three months after the initial surgery.